The Use of Social Media as a Promotional Tool to Increase Revenue for Makeup Businesses - Riska Yusgianti; Yuniman Zebua; Syukron Arjuna (Advances in Economics & Financial Studies, 2026)
Purpose: This study aims to analyze the effect of social media use as a promotional tool on increasing the revenue of Suryanti Make Up in Bilah Hilir District, Indonesia. Research Method: This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 130 respondents who had used Suryanti Make Up’s services and were aware of its promotional activities on social media. The independent variable was social media use, while the dependent variable was business revenue growth. Data were analyzed using validity and reliability tests, classical assumption tests, and simple linear regression, with assistance from SPSS. Results and Discussion: The results indicate that social media use has a positive and significant effect on business revenue growth. The research instruments were valid and reliable, and the regression model met the assumptions of normality and heteroscedasticity. These findings show that social media can expand promotional reach, increase customer engagement, and strengthen business visibility in the digital era. Implications: Business owners should optimize social media-based promotion to attract customers and increase revenue. Originality: This study contributes empirical evidence on the role of social media promotion in increasing revenue within the makeup services industry in a local business context.